Peranan Kegiatan Ibu-Ibu PKK Lansia Pada Digitalisasi Kampung - Kartini; Ratna Yulistiani; Rizky Fatkhur Rohman; Achmad Arbi Hanafi; Nabila Dwi Rahma; Daffa Rossi Ifanka (Ikatan Ahli Informatika Indonesia, 2025)
This activity aims to provide training and assistance to PKK women in Menur Pumpungan RT 07 RW 04 in introducing and using websites as information and communication media. The use of information technology is very important to support various activities. Through this activity, participants were introduced to the basics of creating, managing, and utilizing websites. Qualitative research was conducted because the community service program must have an object and place for the implementation of the program. The group work method was used to find out and gather information from the research subjects. These methods include assessment, planning, and evaluation. Researchers and members became the main instruments. While PKK women became supporting instruments in the research. The research was conducted in several stages, which include: 1) planning, 2) implementation, 3) evaluation. In the planning process, researchers and members used several processes in the implementation stage which included: 1) pre-test, 2) website introduction education, 3) elderly health education, 4) post-test. The evaluation resulted in website education, enabling the participants to contribute to the development of the Menur Pumpungan Family Welfare Movement (PKK). Digitizing PKK activities has significantly increased the understanding of technology, particularly websites, among women, including the elderly. Women who were previously unfamiliar with websites now understand their functions and uses. They also learned about the dangers of website misuse and how to protect personal data.